RATING OF ECONOMIC ENTITIES ON THE COMPETITIVENESS OF THE ECONOMY: IMPACT OF THE SUSTAINABILITY - Abdullaev Zafarbek Safibullaevich (European Science Publishing, 2025)
This study will be devoted to the analysis of the impact of the sustainability rating of economic entities on the competitiveness of the national economy. The article discusses the concept of sustainability and the criteria for its assessment, as well as the main factors affecting economic stability. The study highlights the importance of forming a sustainability rating based on the financial condition of business entities, market position and performance indicators.
Keywords: Business entities, sustainability rating, competitiveness, financial stability, economic analysis, innovation development, environmental and social sustainability, public policy, entrepreneurship development, national economy.